2006
DOI: 10.1186/ar2088
|View full text |Cite
|
Sign up to set email alerts
|

Novel self-epitopes derived from aggrecan, fibrillin, and matrix metalloproteinase-3 drive distinct autoreactive T-cell responses in juvenile idiopathic arthritis and in health

Abstract: Juvenile idiopathic arthritis (JIA) is a heterogeneous autoimmune disease characterized by chronic joint inflammation. Knowing which antigens drive the autoreactive T-cell response in JIA is crucial for the understanding of disease pathogenesis and additionally may provide targets for antigen-specific immune therapy. In this study, we tested 9 self-peptides derived from joint-related autoantigens for T-cell recognition (T-cell proliferative responses and cytokine production) in 36 JIA patients and 15 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Evidence for auto-reactivity of circulating T cells includes responses to the joint-related proteins aggrecan and fibrillin, the latter primarily in patients with polyarticular JIA. (52) Several heat shock proteins (HSPs) are also potential autoantigens in JIA. Highly conserved across species, HSPs are produced in response to cell stress.…”
Section: Pathogenesismentioning
confidence: 99%
“…Evidence for auto-reactivity of circulating T cells includes responses to the joint-related proteins aggrecan and fibrillin, the latter primarily in patients with polyarticular JIA. (52) Several heat shock proteins (HSPs) are also potential autoantigens in JIA. Highly conserved across species, HSPs are produced in response to cell stress.…”
Section: Pathogenesismentioning
confidence: 99%
“…rheumatoid factor positive (RF+)poly-JIA and adult RA, s-JIA and adult Still's disease [2,3]. High numbers of autoreactive T cells within the joint of poly-JIA patients indicate an antigen-driven activation of the adaptive immune system [4]. However, the typical clinical signs of s-JIA are rather associated with granulocytosis, thrombocytosis and increase of acutephase reactants in the peripheral blood, indicating an uncontrolled activation of the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The association between susceptibility to oligoarticular JIA and HLA class II alleles implicates CD4 + T cells in the pathogenesis of chronic arthritis [3]. This is supported by the fact that activated CD4 + T cells clustered around dendritic cells are found in the synovia of the inflamed joint in oligoarticular JIA patients [4]. There exist two hypotheses for the development of autoimmune phenomena in oJIA: Massa et al reported that T cell cross-recognition (molecular mimicry) of exogenous and self HLA-derived antigens generates an abnormal regulatory circuit which maintains and expands T cells, which may participate in autoimmune inflammation by generation of pro-inflammatory cytokines [5].…”
Section: Introductionmentioning
confidence: 94%
“…There exist two hypotheses for the development of autoimmune phenomena in oJIA: Massa et al reported that T cell cross-recognition (molecular mimicry) of exogenous and self HLA-derived antigens generates an abnormal regulatory circuit which maintains and expands T cells, which may participate in autoimmune inflammation by generation of pro-inflammatory cytokines [5]. Another hypothesis is that auto-antigens derived from cartilage and other joint-related tissue, such as aggrecan, fibrillin and matrix-metalloproteinase 3 (MMP3), may be able to activate auto-reactive CD4 + T cells, including Th1 and Th17 cells which are correlated with autoimmune symptoms of oligoarticular JIA [4] [6] [7]. Recent studies suggest that Th17 cells producing pro-inflammatory IL-17 are crucial for initiation and maintenance of autoimmune arthritis in oligoarticular JIA [8].…”
Section: Introductionmentioning
confidence: 99%